Zeitdiagnose Männlichkeiten Schweiz - AG Transformation von Männlichkeiten (Gender Issues, 2021)
Change and persistence of gender relations in the workplace, family, and politics create specific opportunities and challenges for men and masculinity(ies). What is currently changing at all is up for debate. What developments are identified? What potentials, contradictions, and tensions - for men and for society - open up or emerge as a result? How have masculinities evolved and been shaped historically in Switzerland? The book brings together research papers on masculinity(ies) in Switzerland that contribute to a critical contemporary analysis. Perspectives from different disciplines are included: gender studies, sociology, social work, history, literary studies, psychology, and migration studies.